Proposal of teaching activities with an interdisciplinary approach in the subject Physical Geography III - Rodriguez Lence , Yaité; Domínguez Pacheco , Danay; Suárez Pérez , Yamirka; Rodríguez Armada, Yaneysi (Revista Minerva, 2021)
The interdisciplinary relationship is an important tool when dealing with Geography contents that constitute part of the curriculum of the regular university program, to contribute to the continuous education in this educational level. Even though, there are still difficulties in the results obtained on this aspect in the teaching-learning process. Due to this, the present paper deals with the importance of the establishment of interdisciplinary relationship between the subjects Physical Geography III and Biological Sciences in the program Biology-Geography, the principles to take into account to enhance the quality of the education process because these relations diminish the double teaching of the same didactic content in different subjects. The end of this work is to apply a set of activities that facilitate the interdisciplinary relationship starting from the needs assessment about the application of this principle. With the implementation of these activities through interdisciplinary tasks an integrating thought style is obtained and the motivation for curiosity contributes to the students` interest towards investigation and constitutes a necessary condition for course faculty work in Higher Education.